Aplikasi Kontrol Pemakaian Listrik Rumah Tangga Berbasis Web - Safni Marwa; Sunanto (Politeknik Kampar, 2018)
Electrical energy is energy that is very important in human life both for industrial, school and household needs. The source of electrical energy comes from fuels such as oil and gas. Given the depletion of natural resources in the form of oil and natural gas, it is possible that electrical energy will become very expensive. To minimize the use of electrical energy, a control is made to save electricity aimed at household electricity use, because the use of electrical energy in households is generally very large. In order to make it easier to save electrical energy in households, a web-based control is created that uses the web as a transmission medium. This web-based control application utilizes the parallel/db25 port, the port used is the data port from D0-D7. This application can be accessed via mobile phones and computers. This web-based control is equipped with a web server service that is related to electrical equipment in the household.